Epidemiological characteristics of hand, foot and mouth disease in Shenzhen from 2008 to 2020 and effect of inactivated EV71 vaccine on disease incidence - Zhao-yi LIANG; Jun MENG; Yan-wei ZHANG (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo analyze prevalence characteristics of hand, foot and mouth disease (HFMD) in Shenzhen city from 2008 to 2020 and to evaluate the impact of inactivated enterovirus 71 (EV71) vaccination on HFMD incidence for providing evidence to promoting inactivated EV71 vaccination and formulating strategies on HFMD prevention and control. MethodsThe data on HFMD incidence for Shenzhen municipality during 2008 - 2020 were retrieved from China's Infectious Disease Information System and that on inactivated EV71 vaccination were extracted from Childhood Immunization Planning Information System of Shenzhen Municipality; the information on prevalent strains related to HFMD epidemics in the city was collected simultaneously from pathogenic surveillance dataset. Descriptive epidemiological statistics was conducted to analyze prevalence characteristics of HFMD and the effect of inactivated EV71 vaccination on HFMD incidence and prevalent pathogenic strains. ResultsTotally 469 686 HFMD cases were reported during the 13-year period in the city, with an average annual incidence rate of 312.25/100 000. During a year, HFMD incidence was obviously higher in summer season than in winter season, with two incidence peaks in April - July and September - October. Higher incidence rate were observed in the regions with a large number of migrant workers or high population density. The majority of the reported cases were males, children aged 4 years and younger, and homebound children, accounting for 60.54%, 89.69%, and 76.58% of total cases, respectively. The HFMD incidence declined evidently from 516.13/100 000 in 2016 to 84.42/100 000 in 2020 with the yearly increasing of EV71 vaccination rate; the proportion of HFMD cases due to the infection of EV71 also decreased from 16.19% in 2016 to zero in 2020. ConclusionInactivated EV71 vaccination can effectively prevent and control HFMD epidemic, especially for the HFMD epidemic caused by EV71 infection.